2007
DOI: 10.1108/17506180710824154
|View full text |Cite
|
Sign up to set email alerts
|

Exercises in tourism empowerment practice

Abstract: Purpose -The paper's purpose is to provide background and practical exercises for management to gain a perspective on the nature of true employee empowerment. Design/methodology/approach -After a brief overview of the nature of empowerment, a series to training exercises offers insight into how employee empowerment in the tourism industry can create deeper investment in the corporate mission and greater customer service. The exercises also examine approaches for management to avoid. Findings -Employee empowerm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Koelble, 2011;Scheyvens, 1999), sustainable tourism development (e.g. Cole, 2006), employment (Timmerman & Lytle, 2007;Tohidy Ardahaey & Nabiloo, 2012), gender, poverty reduction (Tucker & Boonabaana, 2012), and even topics such as tourist photography (Scarles, 2012).…”
Section: Residents' Perceived Empowerment and Public Trustmentioning
confidence: 99%
“…Koelble, 2011;Scheyvens, 1999), sustainable tourism development (e.g. Cole, 2006), employment (Timmerman & Lytle, 2007;Tohidy Ardahaey & Nabiloo, 2012), gender, poverty reduction (Tucker & Boonabaana, 2012), and even topics such as tourist photography (Scarles, 2012).…”
Section: Residents' Perceived Empowerment and Public Trustmentioning
confidence: 99%
“…In this context, it has been aimed to determine implementation levels of mission, vision and basic values statements, strategic planning processes, benchmarking, outsourcing, total quality management, SWOT analysis, strategic alliances, reengineering, empowerment and information and communication technologies in these enterprises by means of conducting interview with the hotel managers. In the study, strategic management tools have been found to be important in hotel management operations as stated by Abya (2015), Angeloni (2013), Zlatković (2016), Wöber (2002), Timmerman and Lytle (2007), Holjevac (1996), Gajdošíková et al, (2016), Galičić (1996), Buhalis (1998) and Morais et.al., (2016) in the literature. In addition, the study bears resemblance to the research conducted by Şentürk (2012) in the dimension of total quality management approach and has revealed that this strategic management tool is frequently applied in hotel management operations.…”
Section: Conclusion and Recommendationsmentioning
confidence: 86%
“…The concept of consumer empowerment is a much-used one in a wide range of industries -from healthcare (Rapp et al, 1993;Salzer, 1997;Ouschan et al, 2006;Aujoulat et al, 2007), public services (Gilliatt et al, 2000), retailing (Watheieu et al, 2002;Wright et al, 2006;Hunter and Garnefeld, 2008), and travel and tourism (Outi et al, 2007;Timmerman and Lytle, 2007;Füller et al, 2009), to banks and large service organizations (Kark et al, 2003;Liden et al, 2000). From our study of the aforementioned literature, we have found that traveler empowerment in the passenger railway industry is a relatively under-explored area.…”
Section: Conceptual Model Of Traveler Empowermentmentioning
confidence: 89%